Professional versus family management in Brazilian fashion retail companies: exploring value-investors’ perceptions - Clarice Secches Kogut (Cadernos EBAPE.BR, 2017)
Regarding the debate on which sort of management – professional or family administrati on – would more eff ecti vely run businesses, this paper discusses the advantages and shortcomings of family and professional management from a theoreti cal and a practi ti oner’s viewpoint. The study aims at contributi ng to our understanding about the superiority that either type of management might have delivering long- term performance and value creati on to shareholders. Six investors from top value investment funds were interviewed regarding the management of seven fashion retail Brazilian companies. Data analysis revealed that investors do not prefer either type of management – family or professional – when they make investments. Instead, they do look for specifi c characteristi cs and patt erns of behavior in a CEO, which resemble Selznick’s (1957) defi niti on of an insti tuti onal leader. Finally, the paper suggests a new path of research for scholars (relati ng old insti tuti onalism and professionalism) and practi cal guidelines for each type of management (family or professional), off ering, therefore, an academic as well as a practi cal contributi on.